High selective frequency response in a complementary split ring resonator based transmission line. Issue 1 (January 2017) - Zhang, Dawei; Wu, Qun; Sha, Xuejun
ABSTRACT: In this letter, a microstrip line based on complementary split ring resonator (CSRR) technology and coupled with square open‐loop resonator (OLR) is presented. The addition of OLR to the conventional CSRR‐loaded unit cell generates transmission zero in the upper stop band and improves the upper band rejection level without increasing the traversal dimensions. Consequently, a new high selective passband with increased bandwidth and a pair of transmission zeros at both lower and upper sides are formed due to the appropriate couplings among the resonators and the host microstrip line. Moreover, the geometry of the basic cell is quite simple without requiring complex configurations and via holes which is easy to fabricate and low in cost. For demonstration, a two‐stage transmission line prototype is fabricated and tested to experimentally validate the attractive out‐of‐band performance (>36 dB) for filter applications as predicted in theory. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:12–15, 2017